A Combined Set of Four Serum Inflammatory Biomarkers Reliably Predicts Endoscopic Disease Activity in Inflammatory Bowel Disease - Bourgonje, Arno R.; von Martels, Julius Z. H.; Gabriëls, Ruben Y.; Blokzijl, Tjasso; Buist-Homan, Manon; Heegsma, Janette; Jansen, Bernadien H.; van Dullemen, Hendrik M.; Festen, Eleonora A. M.; ter Steege, Rinze W. F.; Visschedijk, Marijn C.; Weersma, Rinse K.; et al. (Frontiers in Medicine, 2019)
Introduction: Blood C-reactive protein (CRP) and fecal calprotectin levels are routinely measured as surrogate markers of disease activity in Inflammatory Bowel Disease (IBD), but often do not correlate well with the degree of mucosal inflammation in the intestine as established by endoscopy. Therefore, novel predictive biomarker(s) are urgently needed that better reflect mucosal disease activity in IBD. The aim of this study was to identify a combination of serum inflammatory biomarkers predictive for endoscopic disease activity. Methods: Serum concentrations of 10 inflammatory biomarkers were analyzed in 118 IBD patients (64 Crohn’s disease (CD), 54 ulcerative colitis (UC)) and 20 healthy controls. In a subset of 71 IBD patients, endoscopic disease activity was established. Nonparametric ROC estimation with bootstrap inference was used to establish the best combination of inflammatory biomarkers predicting endoscopic disease activity. Results: Six (6) inflammatory biomarkers (serum amyloid A (SAA), Eotaxin-1, IL-6, IL-8, IL-17A and TNF-α) showed better prediction of IBD disease activity than routine measures (CRP, fecal calprotectin and HBI/SCCAI scores). The best combination of predictive inflammatory biomarkers consisted of serum SAA, IL-6, IL-8 and Eotaxin-1, showing an optimism-adjusted area under the ROC curve of 0.84 (95% CI: 0.73 – 0.94, P < 0.0001), which predicted significantly better (P = 0.002) than serum CRP levels with an AuROC of 0.57 (95% CI: 0.43 – 0.72, P = 0.32). Conclusion: The combination of SAA, IL-6, IL-8 and Eotaxin-1 reliably predicts endoscopic disease activity in IBD and might be valuable for monitoring disease activity and management of the disease.